EFFECT PROFITABILITY, HEDGING, AND GENDER DIVERSITY TOWARD FIRM VALUE - Asmar Basta; Dewa Putra Krishna Mahardika (Jurnal Ekonomi, 2023)
Firm Value is an investor's assessment of the company's level of success which is often associated with stock prices. The high value of a company is determined by the value of a high stock price, high stock prices can result in a high rate of return to investors. The company's goal is to maximize the value of the company and increase shareholder wealth. This study aims to determine the effect of profitability, hedging, and gender diversity on firm value in coal mining subsector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2021 simultaneously or partially. The data used in this study were obtained from annual reports and financial reports for 2017-2021. The population used in this study are coal mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2021. The technique used in this research is purposive sampling. The statistical analysis used is panel data regression analysis. The research was conducted over a 5 year period with 13 companies obtained, so that a total of 65 observation data were processed.